2017
DOI: 10.1177/1352458517711276
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cellularity of bone marrow in multiple sclerosis with decreased MSC expansion potential and premature ageing in vitro

Abstract: Background:Autologous bone-marrow-derived cells are currently employed in clinical studies of cell-based therapy in multiple sclerosis (MS) although the bone marrow microenvironment and marrow-derived cells isolated from patients with MS have not been extensively characterised.Objectives:To examine the bone marrow microenvironment and assess the proliferative potential of multipotent mesenchymal stromal cells (MSCs) in progressive MS.Methods:Comparative phenotypic analysis of bone marrow and marrow-derived MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 42 publications
0
47
0
Order By: Relevance
“…The negative association between antioxidant responses (SOD1 and GSTP1 secretion) and duration of progressive MS raises the possibility that chronic exposure to disease adversely affects MSC function with functional consequences for the bone marrow microenvironment including, for example, alterations in regulatory and pro‐inflammatory T‐cell populations. While this may, in turn, contribute to disease pathophysiology, the finding adds to our previous work, demonstrating changes consistent with accelerated ageing in MS bone marrow and has clear implications for both MSC‐based and autologous haematopoietic stem cell therapy for MS and other conditions where oxidative stress plays a role in disease . It would suggest that bone marrow‐derived cell therapy is more likely to be effective in MS patients with a shorter phase of progressive disease although, based on currently available data, we are unable to speculate regarding a cut‐off in terms of age or disease duration for consideration of therapy.…”
Section: Discussionmentioning
confidence: 62%
“…The negative association between antioxidant responses (SOD1 and GSTP1 secretion) and duration of progressive MS raises the possibility that chronic exposure to disease adversely affects MSC function with functional consequences for the bone marrow microenvironment including, for example, alterations in regulatory and pro‐inflammatory T‐cell populations. While this may, in turn, contribute to disease pathophysiology, the finding adds to our previous work, demonstrating changes consistent with accelerated ageing in MS bone marrow and has clear implications for both MSC‐based and autologous haematopoietic stem cell therapy for MS and other conditions where oxidative stress plays a role in disease . It would suggest that bone marrow‐derived cell therapy is more likely to be effective in MS patients with a shorter phase of progressive disease although, based on currently available data, we are unable to speculate regarding a cut‐off in terms of age or disease duration for consideration of therapy.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, MSCs can be primed by preexposure to noxious stimuli [44], implying that prolonged stimulation under pathological conditions might be associated with a loss of the putative disease-ameliorating capacity of MSCs. In addition, the age of donors has been considered as a factor that might limit the effectiveness of MSC-based therapy [45,46], particularly autologous MSC therapy. Senescence affects various functions of MSCs [47,48], reduces the capacity for migration and homing [49], and impairs the immunosuppressive potential [50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from the laboratory of Claire M. Rice (Southmead Hospital, Bristol, UK) revealed that MSCs derived from MS patients suffered from an early aging‐like phenotype, displaying reduced expansion and neuroprotective activity and premature senescence in vitro, indicating a potential problem for their in vivo therapeutic application. In a new STEM CELLS Translational Medicine article, Redondo et al now establish that MSCs derived from MS patients display an elevated sensitivity to nitrosative stress (as determined by exposure to DETANONOate, a nitric oxide donor) and the diminished expression, activity, and secretion of antioxidants such as superoxide dismutase 1 (SOD1) and glutathione S‐transferase P (GSTP1). The authors linked the reduced expression of antioxidants to a decrease in expression of master regulators of antioxidant responses (NRF2 and PGC1α) and negatively correlated this downregulation with the duration of the progressive phase of MS.…”
Section: Featured Articlesmentioning
confidence: 99%
“…The anti‐inflammatory, immunomodulatory, and antioxidant activities of MSCs combined with their favorable safety profile have brought hope of an effective stem cell therapy for MS patients; however, we lack a full understanding of how MS and the associated proinflammatory environment affect MSC function. Unfortunately, very recent studies have provided evidence that MSCs derived from MS patients suffer from an early aging‐like phenotype with diminished paracrine neuroprotective abilities . Our second Featured Article from Redondo et al describes how an increased susceptibility to nitrosative stress in combination with the reduced expression, activity, and secretion of antioxidants can contribute to the functional deficits observed in MSCs derived from MS patients.…”
mentioning
confidence: 99%